Study on Techniques for Solving Constrained Optimization Problem - Ahmad, Mobin (IJRDO -JOURNAL OF MATHEMATICS, 2018)
The foundation of optimization techniques can be traced from 300 BC when Euclid recognized the minimum distance between two points to be length of straight line amalgamation the two. He also proved that a square has the greatest area among the rectangles with given total length of edges. Heron proved in 100 BC that light travels between two points through the path with shortest length when reflecting from a mirror. This paper studies on Techniques for Solving Constrained Optimization Problem.